2010
DOI: 10.1016/j.bcp.2010.08.010
|View full text |Cite
|
Sign up to set email alerts
|

(d-Ser2)Oxm[mPEG-PAL]: A novel chemically modified analogue of oxyntomodulin with antihyperglycaemic, insulinotropic and anorexigenic actions

Abstract: Oxyntomodulin (Oxm) is a hormone which has been shown to exhibit a range of potentially beneficial actions for alleviation of obesity-diabetes. However, exploitation of Oxm-based therapies has been severely restricted due to degradation by the enzyme dipeptidylpeptidase-IV (DPP-IV). Thus, the aim of this study was to assess the glucose-lowering, insulin-releasing and anorexigenic actions of chemically modified, enzyme-resistant analogues of Oxm. Oxm, (d-Ser(2))Oxm and (d-Ser(2))Oxm[mPEG-PAL], were incubated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 37 publications
4
42
1
Order By: Relevance
“…In keeping with this, insulin sensitivity was significantly improved by day 28 and this was accompanied by a marked improvement in glucose-mediated insulin secretion. These data clearly support previous suggestions of improved beta cell function and glucose homeostasis following dual activation of glucagon-and GLP-1Rs [13]. Notably we observed a marked expansion of pancreatic islet and beta cell mass, with increased total numbers of islets in (D-Ser 2 )glucagon-exe-treated mice.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In keeping with this, insulin sensitivity was significantly improved by day 28 and this was accompanied by a marked improvement in glucose-mediated insulin secretion. These data clearly support previous suggestions of improved beta cell function and glucose homeostasis following dual activation of glucagon-and GLP-1Rs [13]. Notably we observed a marked expansion of pancreatic islet and beta cell mass, with increased total numbers of islets in (D-Ser 2 )glucagon-exe-treated mice.…”
Section: Discussionsupporting
confidence: 80%
“…This contrasts with the findings of a previous study using a long-acting OXM molecule in ob/ob mice [13]. In the present study body weight, non-fasting circulating glucose, glucose tolerance, insulin sensitivity and pancreatic morphology were still significantly improved in (D-Ser 2 )glucagonexe-treated mice 14 days after cessation of treatment.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Despite the promise of this peptide, such compounds are still susceptible to rapid enzymatic degradation and efficient renal filtration (Holst, 1991). Many studies have demonstrated that PEGylation or fatty acid derivatisation of regulatory peptides results in longer-acting analogues, largely by increased enzymatic stability and reduced renal clearance through binding to plasma proteins (Knudsen et al, 2000;Lee et al, 2006;Gault et al, 2008;Kerr et al, 2009Kerr et al, , 2010. Building on these approaches to stabalise related regulatory hormones, we have developed two novel glucagon analogues, namely desHis 1 Glu 9 -glucagon-[mPEG] and desHis 1 Glu 9 (Lys 30 PAL)-glucagon.…”
Section: Introductionmentioning
confidence: 99%